Pavement materials - National Association of Australian State Road Authorities (Sydney : Association of Australian State Road Authorities, 1976)
Pt 1 Search -- pt 2 Natural gravel, sand-clay and soft and fissile rock -- pt 3 Crushed rock -- pt 4 aggregates